Mixed finite element methods for steady granular flows : numerical analysis and applications - Medrado, Saulo Rodrigo (2025)
Tese (doutorado) — Universidade de Brasília, Departamento de Matemática, Mestrado Profissionalizante em Matemática, 2025.